(untitled) (Research, Society and Development, 2020)
Objective: describe the development of protocols and flowcharts for the implementation of kanban in the urgency and emergency sector. Methodology: action research carried out in six seminars with six members of the regulatory sector and three of the urgency and emergency of a university hospital in the southeastern region of Brazil between May 21, 2018 to May 31, 2019. Data were recorded, transcribed and submitted to Bardin’s content analysis. Results: they defined the kanban for bed management and organized the implementation and implementation through protocols, flowcharts and the development of software for monitoring the kanban tool. Conclusion: the study made it possible to systematize steps and resources for implementing kanban in the urgency and emergency sector, which, in health, does not have a standardized methodology. Therefore, this study may guide the expansion of the tool to other sectors at the local level, making appropriate adjustments and influencing researchers from other institutions.